Green formulation strategy for preparing oil-in-water emulsions via lipase-catalyzed transesterification - Natcha Wongthongdee (2018)
© 2016 American Chemical Society. Formulation of submicronic diglyceride-inwater emulsions was carried out without addition of synthetic surfactant in case of commercial caprylic/capric diglyceride. Sugar surfactant was prepared by contacting the oil with a concentrated aqueous solution of sorbitol (70 wt %) containing lipase AY. Interfacial lipase-catalyzed transesterification took place and led to limited but sufficient amounts of sorbitol ester and monoglyceride, which accumulated in the oil. The enzyme-treated oil could be easily separated from the aqueous phase and used for preparing oil-in-water emulsion without adding any other surfactant. A stable emulsion was obtained for at least 7 days and exhibited better stability at 60 °C than Tween 20-stabilized emulsion.